Employment, income distribution, and development strategy : problems of the developing countries : essays in honour of H. W. Singer - Singer, H. W.; Cairncross, Alec; Puri, Mohinder (London : Macmillan, 1976)
This book is a collections of essays by a distinguished group of economists from many different countries published in celebration of the sixty-fifth birthday of Hans Singer who, after twenty-two years with the United Nations in New York is now Professorial Fellow at the Institute of Development Studies and Professor of Economics at the University of Sussex. The contributions fall into three groups. First come six papers on the distribution of income in the process of development or on the related issue of employment opportunities. The next seven papers discuss various aspect of development strategy including industrialization, the role of capital goods, collective self-reliance and population policy. Finally are four miscellaneous papers on problems ranging from food aid to India's experience of economic management. A full bibliography of Professor Singer's writings is given at the end of the book.
Includes indexes.
"List of H. W. Singer's publications": p. 245-253.
rpm 05/04/2018
Loans
Keywords: Singer, H. W; Economic development; Income distribution